Un manifeste de l'occidentalisation dans la Turquie kémaliste : Üç medeniyet (Trois civilisations) (1928) - François Georgeon (Revue des Mondes Musulmans et de la Méditerranée)
Kemalist reforms in Turkey aimed at entering the country into civilization. Intellectual and political elites were deeply influenced by Ziya Gökalp (died in 1924) who thought that there was one universal civilization whose material and technical aspects should be imitated and specific national cultures whose moral and spiritual values should be kept. He also justified change by referring to custom (örf), a notion that was used by Muslim jurists in the past. Some thinkers nevertheless had different ideas, especially Ahmed Ağaoğlu (1869-1939), a writer and a politician who, in 1928, published a book entitled Üç medeniyet (The Three Civilizations). This book both criticizes Ziya Gökalp's thought and political centralization and despotism. Ahmed Ağaoğlu believed that social Islamic institutions had definitely failed and that Turkish people should abandon the past and take on Western civilization as a whole. He advocated the separation of politics and religion and a complete individual emancipation. Although he was criticized for his polemical tone, he had original views for his time. He was a liberal supporter of the reforms. This liberalism has found new echoes in Turkey since the 1980's.